A RESCUE THERAPY FOR PERSISTENT OPTIC DISK PIT MACULOPATHY IN PREVIOUSLY VITRECTOMIZED EYES. Issue Volume 12:Issues 1(2018) (2018) - Figueroa, Marta S.; Nadal, Jeroni; Contreras, Inés
Abstract : Purpose: To report the results of vitrectomy with platelet-rich plasma (PRP) application and gas tamponade as a rescue therapy in previously vitrectomized eyes with optic disk pit (ODP) maculopathy. Methods: Three patients with visual loss due to persistent or recurrent ODP maculopathy who had undergone previous vitrectomy were offered application of PRP. Platelet-rich plasma was obtained by centrifugation of a blood sample from each patient. Surgery consisted of vitrectomy and internal limiting membrane peeling if the membrane had not been already removed (in two eyes). After fluid/air exchange, three drops of PRP were applied on the ODP followed by 8% C3F8 tamponade. Immediately after surgery, the patient remained supine for 30 minutes and then kept a face-down position for 2 weeks. Results: Optic disk pit maculopathy improved as soon as two weeks after surgery and resolved in all eyes between six and eight months after PRP application. Patients were followed up for three years, with no recurrences. Visual acuity remained stable in one eye and improved in two eyes. Conclusion: Vitrectomy with PRP application may be useful as a rescue therapy in patients with refractory ODP maculopathy. Platelet-rich plasma may act by promoting the closure of the communication between the vitreous and the intraretinal/subretinal space at the pit. This treatment may avoid potentially harmful maneuvers that have been used to treat ODP maculopathy. Abstract : Supplemental Digital Content is Available in the Text.The application of platelet-rich plasma (PRP) on the optic disk pit (ODP) followed by gas tamponade leads to resolution of persistent or recurrent ODP-maculopathy in previously vitrectomized eyes. Platelet-rich plasma may act by promoting the formation of scar tissue at the anomalous communication between the vitreous and retina at the ODP.